Molecular biology of the gene - Watson, James D.; Watson, James D.; Bell, Stephen P.; Gann, Alexander; Levine, Michael; Baker, Tania A. (Boston Pearson, 2014)
The long-awaited new edition of James D. Watson's classic text, Molecular Biology of the Gene, has been thoroughly revised and is published to coincide with the 50th anniversary of Watson and Crick's paper on the structure of the DNA double-helix. Twenty-one concise chapters, co-authored by five highly respected molecular biologists, provide current, authoritative coverage of a fast-changing discipline, giving both historical and basic chemical context. Divided into four parts: Genetics and Chemistry, Central Dogma, Regulation, and Methods. For college instructors, students, and anyone interested in molecular biology and genetics.
Include bibliographical references.; Appendices 793-844p.; Index 845-872p.
Keywords: Genome; Macromolecules; Molecular biology; Zoology